Laplace Transform of Some Hypergeometric Functions - Poudel, Madhav Prasad; Harsh, Harsh Vardhan; Pahari, Narayan Prasad (Nepal Journal of Mathematical Sciences, 2023)
The hypergeometric functions are one of the most important and special functions in mathematics. They are the generalization of the exponential functions. Particularly the ordinary hypergeometric function 2F1(a, b; c; z) is represented by hypergeometric series and is a solution to a second order differential equation. Similarly, Laplace transform is a form of integral transform that converts linear differential equations to algebraic equations. This paper aims to study the convergence of hypergeometric function and Laplace transform of some hypergeometric functions. Moreover, some relationships between Laplace transformation and hypergeometric functions is established in the concluding section of this paper.